Root Canal Anatomy and Morphology of Mandibular First Molars in a Selected Iranian Population: An In Vitro Study - Akhlaghi, Nahid Mohammadzadeh; Khalilak, Zohreh; Vatanpour, Mehdi; Mohammadi, Saman; Pirmoradi, Sakineh; Fazlyab, Mahta; Safavi, Kamran (Iranian Endodontic Journal, 2016)
Introduction: The aim of this study was to evaluate root canal anatomy of mandibular first molars (MFM) in a selected Iranian Population using clearing technique. Methods and Materials: A total of 150 extracted MFMs were cleared. The root canal morphology (including the root numbers and root length) and the anatomy of the root canal system (including is the number and type of canals based on Vertucci’s classification, canal curvature according to Schneider’s method and the presence of isthmus) was evaluated using the buccolingual and mesiodistal parallel x-rays and stereomicroscope. The data were analyzed using the chi-square test. Results: Two and three roots were present in 96.7% and 33% of the teeth, respectively (P=0.0001). All the teeth (100%) had two canals in the mesial root, while 61.3% of the samples had one distal root canal (P=0.006). The root canal configuration in the mesial canal included type IV (55.3%) and type II (41.3%) (P=0.0001). In doubled-canalled distal roots, 68.8% and 24.3% were type II and type IV, respectively (P=0.0001). Isthmii were observed in 44.6% of mesial and 27.3% of distal roots (P=0.0001). Conclusion: The notable prevalence of type IV configuration in both roots of mandibular first molars, presence of isthmus and root curvature, necessitates the careful negotiation and cleaning of all accessible canal spaces. Keywords: Iranian Population; Mandibular First Molar; Root Canal Anatomy; Root Canal Morphology; Tooth Clearing